Low H3K27me3 deposition at CYP82E4 determines the nicotinic conversion rate in Nicotiana tabacum - Song, Shiyang; Wang, Yaqi; Wang, Jin; Liu, Yanfang; Zhang, Xingzi; Yang, Aiguo; Li, Fengxia (Plant physiology and biochemistry, 2024)
Nicotine conversion is the process by which nornicotine is synthesized from nicotine. The capacity of a plant to carry out this process is represented by the nicotine conversion rate (NCR), which is defined as the percentage of nornicotine content out of the total nicotine + nornicotine content. Nicotine conversion in tobacco is mediated by CYP82E4. Although there are cultivar-specific differences in NCR, these do not correspond to differences in the CYP82E4 promoter or gene body sequences, and little is known about the underlying regulatory mechanism. Here, we found that histone H3 Lysine 27 trimethylation (H3K27me3) was involved in CYP82E4 expression, functioning as a transcriptional repressor. Compared to a high-NCR near-isogenic line, a low-NCR cultivar showed increased levels of the repressive histone modification markers H3K27me3 and H3K9me3 at CYP82E4. Comparison of histone markers between several cultivars with varying NCRs showed that H3K27me3 and H3K9me3 levels were significantly associated with cultivar-specific differences in NCR. Treatment with the H3K27me3 demethylase inhibitor GSK-J4 increased total H3K27me3 levels and enriched H3K27me3 at the CYP82E4 locus; the increased levels of H3K27me3 further inhibited CYP82E4 expression. Knocking out E(z), an indispensable gene for H3K27me3 formation, decreased H3K27me3 levels at CYP82E4, leading to a more than three-fold increase in CYP82E4 expression. Changes in CYP82E4 expression during leaf senescence and chilling stress were also strongly correlated with H3K27me3 levels. These findings reveal a strong correlation between CYP82E4 expression and histone modifications, and demonstrate an instance of histone-mediated alkaloid regulation for the first time. •Plants with a high nicotine conversion rate had lower levels of H3K27me3 and H3K9me3 at CYP82E4.•Treatment of tobacco seedlings with the H3K27me3 demethylase inhibitor GSK-J4 inhibited CYP82E4 transcription.•Knocking out E(z) increased CYP82E4 expression by more than three-fold.•Leaf senescence and chilling stress affected H3K27me3 modifications at CYP82E4.